Improving Poetry Writing Skills Using the Example Non-Example Learning Model - Kelutur, Sani; Sapulette, Viona (Universitas Pattimura, 2025)
An effective learning method is essential for students to develop writing skills, particularly in poetry composition, which represents a crucial component of the Indonesian language curriculum. This study aims to enhance the poetry writing skills of Grade VIII-A students at SMP PGRI Belis, Teluk Waru District, East Seram Regency, through the implementation of the Example Non-Example Learning Model. Using Classroom Action Research (CAR) methodology, this study employed a cyclical process encompassing planning, execution, observation, and reflection across two cycles. The research involved 23 students (8 males and 15 females). Initial results from Cycle I revealed that 14 students (61%) had not achieved the Minimum Competency Criteria (MCC) of 70, while only 9 students (39%) met the criteria. Following the implementation of the example non-example learning model in Cycle II, significant improvement was observed: 20 students (87%) achieved the MCC, while only 3 students (13%) did not meet the criteria, resulting in an average score of 80.21, categorized as